Don't read the comments - Smith, Eric (Eric A.) (Inkyard Press, 2021)
An elite gamer who uses her status to secure sponsorships to help her struggling family and a fellow player who resists his mom's ambitions for his future find their virtual worlds and blossoming romance challenged by malicious trolls.